Exploring Cross-Cultural Management Practices in Global Organizations: A Qualitative Study - Farah Qalbia; Muhammad Rizal; Ngadi Permana (LPPM STIE Kasih Bangsa, 2024)
This qualitative study aims to investigate cross-cultural management practices within global organizations. The research seeks to understand the dynamics of cultural diversity in management and its impact on organizational effectiveness. Employing a qualitative research model, data was collected through semi-structured interviews with managers and employees from diverse cultural backgrounds within multinational corporations. Sampling techniques involved purposive sampling to ensure representation across cultures. Data analysis utilized thematic analysis, identifying patterns and themes within the interviews. The study found that effective cross-cultural management involves embracing diversity, fostering intercultural communication, and implementing flexible strategies tailored to specific cultural contexts. These findings underscore the importance of cultural sensitivity and adaptability in enhancing organizational performance and fostering a harmonious work environment in global settings.